Upaya Pengenalan Editorial Dan Penulisan Jurnal Ilmiah Pada Tenaga Pendidik Di SMP Negeri 2 Kampar Kiri Hilir Kabupaten Kampar - FATKHURAHMAN, FATKHURAHMAN; HADIYATI, HADIYATI (Komunitas Manajemen Kompetitif, 2017)
Abstract: Partner situation analysis, teachers become professional educators especially for those who have already obtained teacher certification. Teachers in managing rank to level Va to Vb are required to write scientific articles published to scientific journals for the results of his work can be read by various circles in need. The problem of partners, teachers still do not know the scientific editor in order to publish the script, still the lack of knowledge of teachers on how to submit a scientific script to the editorial of scientific journals to be published to scientific journals. Submission of scientific manuscripts is the first step of the teacher in order to publish his scientific work during teaching. During this time the teacher is still less understanding what is a scientific journal and also how to submit a scientific script to the editor to be published to scientific journals. Outcome targets to be achieved in this activity is a form of change of knowledge and ability of teachers as educators to the submission of scientific manuscripts to the editor to be able to publish scientific manuscripts to scientific journals. The solution given in this activity is to provide training in the submission of scientific manuscripts to the editorial to be published to scientific journals. Based on the results of the devotion that has been implemented on December 15, 2016, it was found that information about the change of knowledge of teachers about what is the publisher of scientific journals, the usefulness of the publisher, the submission of the manuscript to the publisher and how the strategy of writing articles to be published to journal publishers. Keywords: The introduction of editorial scientific journals